SISTEM INFORMASI POS PELAYANAN TERPADU BERBASIS WEBSITE MENGGUNAKAN METODE EXTREME PROGRAMMING - Ermawati, Erni; Indriyanti, Indriyanti; Ichsan, Nurul; Wahyuni, Tri; Fatah, Haerul (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2024)
The problem in this research is that the technical notification of Posyandu schedules is still done verbally by word of mouth among the community and is also only announced via loudspeakers at local mosques. This method makes the dissemination of information related to the Posyandu schedule less effective. The main problem that often arises is that there are still parents who don't know the Posyandu schedule, there are even parents who forget the Posyandu schedule. The aim of this research is to make it easier for cadres to convey information and make it easier for parents to receive information about posyandu activity schedules via WhatsApp Blast. This research uses the Extreme Programming method which consists of 4 stages, namely planning, designing, coding and testing. Extreme Programming is a method that is considered effective in its application because it can produce a system that is fast and responsive to changing needs. The result of this research is a posyandu information system based on WhatsApp Blast which was created based on extreme programming stages. Functional testing using the Black Box method shows that the system has met expectations.